Dynamics of COVID-19 epidemic via two different fractional derivatives - Kumar, Pushpendra; Erturk, Vedat Suat; Govindaraj, V; İnç, Mustafa; Abboubakar, Hamadjam; Nisar, Kottakkaran Sooppy (World Scientific Publ Co Pte Ltd, 2023)
In December 2019, the novel Coronavirus, also known as 2019-nCoV or SARS-CoV-2 or COVID-19, was first recognized as a deadly disease in Wuhan, China. In this paper, we analyze two different nonclassical Coronavirus models to observe the outbreaks of this disease. Caputo and Caputo-Fabrizio (C-F) fractional derivatives are considered to simulate the given epidemic models by using two separate methods. We perform all required graphical simulations with the help of real data to demonstrate the behavior of the proposed systems. We observe that the given schemes are highly effective and suitable to analyze the dynamics of Coronavirus. We find different natures of the given model classes for both Caputo and C-F derivative sense. The main contribution of this study is to propose a novel framework of modeling to show how the fractional-order solutions can describe disease dynamics much more clearly as compared to integer-order operators. The motivation to use two different fractional derivatives, Caputo (singular-type kernel) and Caputo-Fabrizio (exponential decay-type kernel) is to explore the model dynamics under different kernels. The applications of two various kernel properties on the same model make this study more effective for scientific observations.
Keywords: Coronavirus/COVID-19; mathematical model; numerical solution; Caputo and Caputo-Fabrizio fractional derivatives; existence and uniqueness